Attracting and Maintaining Generation Y Customer (Case Study: The Body Shop in Bandung) - Qualdi, Muhammad Qareza; Wandebori, Harimukti (Journal of Business and Management, 2013)
The Body Shop is facing a fierce competitive market in C&T industry along with face shop and local brand such as Mustika Ayu Martha Tilaar. Generation Y (people who was born between 1988-1994) become very attractive due to its large market size and high spending power. Ignore this segment will be a huge lost for The Body Shop. The purpose of this study is to analyze marketing strategy that can lead to maintain Ã¢â‚¬Å“Generation YÃ¢â‚¬Â customerÃ¢â‚¬â„¢s The Body Shop in Indonesia. Basic understanding of the marketing strategy, consumer behavior, marketing mix, service quality, customer satisfaction &loyalty used as basic theories. Marketing mix and service quality linked with customer satisfaction & loyalty indicators to get the results of the research . The methodology contains of research framework and determining sampling method. There are descriptive and regression analysis presented in data analysis. Finally, conclusion and recommendation were written based on data analysis and several necessary facts from interview and observation.Ã‚Â Keywords : Generation Y, The Body Shop, Marketing Mix, Service Quality, Customer Loyalty.Ã‚Â